The relationship between abdominal fat and sleep quality after combined exercise in patients with type 2 diabetes mellitus - Han, Yu; Han, Yue-Xia; Huang, Fang; Zou, Hui-Ming; Gu, Qing; Hu, Xue; Fang, Jing-Xian; Meng, Jian; Wang, Sui-Jun (Frontiers in Endocrinology, 2025)
BackgroundExercise holds promise as a non-pharmacological intervention for improving sleep quality. Therefore, this study investigated the potential relationship between abdominal fat and sleep quality after combined exercise in patients with T2DM (Type 2 diabetes mellitus).Material and methodsA total of 100 adults with T2DM (52 women, 48 men), aged 55-75years, were enrolled in the study who were sufficiently active and physically fit were recruited and were randomized equally into four groups: a control group, an AEX group (aerobic exercise), a REX group (resistance exercise) and a COMB group (combination exercise). Patient sleep monitoring reports were collected using a smart bracelet. After 12 weeks of intervention, the Pittsburgh Sleep Quality Index (PSQI) total score, total sleep time, sleep efficiency, time to reawakening, BMI (body mass index), FBG (fasting blood glucose), HOMA-IR (insulin resistance index), HbA1c (glycosylated hemoglobin), VAT (visceral adipose tissue), SAT (subcutaneous adipose tissue), and LBM (lean body mass) were compared among the four groups.ResultsAll exercise training programs improved the PSQI score in patients with type 2 diabetes. COMB is the only training that improves objective sleep quality and quantity, including total sleep time, sleep efficiency, and wake time after sleep onset.ConclusionA comprehensive exercise program to reduce abdominal fat can benefit metabolic and sleep health in people with type 2 diabetes.